2014
DOI: 10.2135/cropsci2014.02.0143
|View full text |Cite
|
Sign up to set email alerts
|

Environment, Harvest Regimen, and Ontogeny Change Lespedeza cuneata Condensed Tannin and Nitrogen

Abstract: Condensed tannins (CT) from sericea lespedeza [Lespedeza cuneata (Dumont de Courset) G. Don], a hardy and widely adapted forage legume, have potential for methane emission suppression, rumen protein bypass, gastrointestinal nematode suppression, and pest fly suppression in ruminants. Nitrogen (N) from this herbaceous legume can also be an important component of crude protein in ruminant diets. The concentrations and yields of CT and N, however, have not been studied across a wide range of environments, harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…It is possible that this issue of variability caused by the different factors is also important for growing sericea lespedeza (Muir et al, 2014), or for the leaves of L. leucocephala or Manihot esculenta that originate from plantations in tropical zones. Variation of PSM contents may be even more evident in plants that grow in the native vegetation.…”
Section: Inherent Variability Of Nutraceutical Plant Materialsmentioning
confidence: 99%
“…It is possible that this issue of variability caused by the different factors is also important for growing sericea lespedeza (Muir et al, 2014), or for the leaves of L. leucocephala or Manihot esculenta that originate from plantations in tropical zones. Variation of PSM contents may be even more evident in plants that grow in the native vegetation.…”
Section: Inherent Variability Of Nutraceutical Plant Materialsmentioning
confidence: 99%
“…S ericea lespedeza [ Lespedeza cuneata (Dumont de Courset) G. Don, SL] has many uses as an herbaceous perennial legume (Mosjidis, 1996, 2010; Muir et al, 2014). Its wide adaptation has resulted in naturalization throughout much of the southeastern United States of America (Hoveland et al, 1990; Diggs, Jr., et al, 1999), to the point that it outcompetes native species in some ecosystems (Mantz et al, 2013; Coykendall and Houseman, 2014).…”
mentioning
confidence: 99%
“…If grown and sold for its CT concentration, however, we need to determine how variable this is over wide environmental ranges, especially latitude, altitude, and climate. We also need to understand how growing season progression may interact with environment to affect not just yield (Muir et al, 2014) but nutritive values and CT concentration as well. The latter could be particularly important if AU Grazer is valued more for its CT than for its more traditional nutritive values, such as CP or digestibility.…”
mentioning
confidence: 99%
“…The decrease in SL PPP contents between harvests for all species with the exception of Intensity 3 and 100% clip suggests that lower-intensity treatments were not adequate to achieve responses similar to what other studies on SL have observed (Donnelly and Anthony 1983;Muir et al 2014). The greater intensity treatments that resulted in biomass loss similar to mowing or cutting for hay that previous studies have used as treatments could explain the variation in results , as could variations in timing of those treatments (Nykänen and Koricheva 2004).…”
Section: Discussionmentioning
confidence: 53%
“…Proanthocyanidins include polymers of phenolic acids (ellagic acid) called tannins (Levin 1971;Chung et al 1998;Khoddami et al 2013). Within plants, tannins vary widely in concentration (Mosjidis et al 1990), structure (Fahey and Jung 1989;Chung et al 1998), allocation (Mosjidis et al 1990;Haring et al 2007), and other characteristics, which may result from the age of the plant (Stitt and Clarke 1941;Buntin 1991;Cooper et al 2014), stresses (Feeny 1976;Fales 1984;Tharayil et al 2011), or season (Stitt and Clarke 1941;Fahey and Jung 1989;Muir et al 2014).…”
Section: Introductionmentioning
confidence: 99%